A dispersed polycrystalline phase boundary constructed in CaZrO3 modified KNN based ceramics with both excellent piezoelectric properties and thermal stability. Issue 10 (15th May 2023) - Huo, Xiangtao; Wang, Facheng; Zhang, Tianhua; Zhang, Mei; Guo, Min
Abstract: In this paper, the ceramics with composition of (0.98- x )(K0.5 Na0.5 )(Nb0.96 Sb0.04 )O3 -0.02(Bi0.5 Na0.5 )(Zr0.8 Ti0.2 )O3- x CaZrO3 (abbreviated as (0.98- x )KNNS-0.02BNZT- x CZ, x  = 0, 0.01, 0.015, 0.02, 0.025, 0.03) were prepared by a traditional solid-state reaction method. The effect of the additional amount of CaZrO3 on the phase structure, microstructure, dispersion index, domain structure and piezoelectric properties of ceramics was systematically studied. Finally, the piezoelectric properties and thermal stability of ceramics could be controlled by adding different amounts of CaZrO3 . The addition of CaZrO3 transferred the phase structure of the ceramics from orthogonal-tetragonal (O-T) coexistence phase to rhombohedral-orthogonal (R–O) coexistence phase, which could be demonstrated by XRD test, temperature-dependent Raman spectra and ε r ‐ T plot analysis. And when x  = 0.02, the ceramics possessed the best piezoelectric and dielectric properties ( d 33  = 253 pC/N, ε r  = 1185, tan δ  = 0.044). Such excellent electrical properties could be originated from the heterogeneous domain structure and small-size nano-domains of the ceramics. Moreover, with the increase of CaZrO3 doping amount, the dispersion index of ceramics gradually increased from 1.404 to 1.871, which showed more obvious dispersion phase transition characteristics and improved the thermal stability of ceramics. Particularly, when x  = 0.02, after annealing at a high temperature of 220 °C (close to its Curie temperature), the d 33 tested at room temperature remained above 85% of that without annealing. The results indicated that (0.98- x )KNNS-0.02BNZT- x CZ ceramic was a promising lead-free piezoelectric ceramic system.